1990
DOI: 10.1007/bf00052607
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages and cancer

Abstract: The uncontrolled growth of metastases resistant to conventional therapeutic modalities is a major cause of death from cancer. Data from our laboratory and others indicate that metastases arise from the nonrandom spread of specialized malignant cells that preexist within a primary neoplasm. These metastases can be clonal in their origin, and different metastases can originate from different progenitor cells. In addition, metastatic cells can exhibit an increased rate of spontaneous mutation compared with benign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
4

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(38 citation statements)
references
References 137 publications
1
33
0
4
Order By: Relevance
“…The same could be true for their infiltration of tumors, and we do detect fewer macrophages infiltrating tumors growing in integrin-or selectin-deficient mice, although the numbers of circulating monocytes͞macrophages do not differ among the strains of mice (15). Macrophages have been suggested to be tumoricidal (36)(37)(38)(39), although other reports have suggested that they also can contribute to tumor growth (40-42); they probably have both effects (42)(43)(44)(45)(46).…”
Section: Discussionsupporting
confidence: 51%
“…The same could be true for their infiltration of tumors, and we do detect fewer macrophages infiltrating tumors growing in integrin-or selectin-deficient mice, although the numbers of circulating monocytes͞macrophages do not differ among the strains of mice (15). Macrophages have been suggested to be tumoricidal (36)(37)(38)(39), although other reports have suggested that they also can contribute to tumor growth (40-42); they probably have both effects (42)(43)(44)(45)(46).…”
Section: Discussionsupporting
confidence: 51%
“…The coated filters were prepared by using Matrigel suspensions at 250 μg/ml. B16 melanoma cells (25x10 3 ) suspended in 200 μl DMEM 4500 containing 250 μg/ml BSA were seeded in the upper chamber and incubated for 18-24 h. After incubation, cells on the upper side of the filters were wiped off and the membranes were fixed overnight in ice-cold methanol. Cells on the lower side of the membranes were stained with Diff Quick and counted.…”
Section: Methodsmentioning
confidence: 99%
“…Among the various types of host cells, tumor-associated macrophages (TAMs) play a critical role in tumor progression. Whereas TAMs may destroy tumor cells following their activation (3,4), they may also produce growth factors, cytokines and proteases that promote invasion and metastatic diffusion of tumor cells (5)(6)(7)(8)(9)(10)(11)(12)(13). It is of particular interest that the failure to recruit macrophages into the tumor microenvironment in colony stimulating factor-deficient (CSF op /CSF op ) mice reduced the metastatic spread of transplanted mammary cancer (14).…”
Section: Introductionmentioning
confidence: 99%
“…Aspects of tumor cells, such as deformibility (Sato and Suzuki, 1976), aggregation (Nicolson, 1986), and cell surface adhesion molecules (Hofmann et al, 1991;Frixen et al, 1991), and those of the host, such as blood turbulence (Sato and Suzuki, 1976;Weiss and Dimitrov, 1986), platelets (Sugimoto et al, 1987;Tsuruo et al, 1986), T-cells (Wiltrout et al, 1979), natural killer cells (Hanna and Fidler, 1980;Herberman, 1989), and macrophages (Fidler, 1985;Whitworth et al, 1990), all contribute to the destruction or survival of blood-borne tumor emboli. Moreover, the passage of tumor cells through capillaries leads to cell lysis by sheer force of movement (Sato and Suzuki, 1976;Weiss and Dimitrov, 1986) and by nitric oxide (NO) produced by cytokine-activated endothelial cells (Li et al, 1991a, b;Geng et al, 1996).…”
Section: Introductionmentioning
confidence: 99%